DISMISSAL BASED ON USE OF SOFTWARE FOR MONITORING EMPLOYEES’ WORK - Božičić, Darko M (Glasnik Advokatske komore Vojvodine, 2022)
The widespread use of information technology has significantly changed how people live and work. Modern production relations can not be imagined without the presence of various IT solutions in the work process. Their main feature is that they speed up and facilitate the work process itself, making it more productive. However, the use of such technology also raises various legal issues. One of them concerns the application of various software solutions for monitoring employees’ work. The data obtained by the employer using such software solutions can lead to dismissal. With this paper, we tried to point out the key employment law issues in the termination of employment contracts due to use of various software for monitoring the performance of employees, as well as to offer answers to overcome them.